Linear carbon chains inside multi-walled carbon nanotubes: Growth mechanism, thermal stability and electrical properties - Kang, Cheon-Soo; Fujisawa, Kazunori; Ko, Yong-Il; Muramatsu, Hiroyuki; Hayashi, Takuya; Endo, Morinobu; Kim, Hee Jou; Lim, Daun; Kim, Jin Hee; Jung, Yong Chae; Terrones, Mauricio; Dresselhaus, Mildred S.; et al. (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
Linear carbon chains (LCCs) consisting of sp-hybridized carbon atoms are considered a fascinating 1D system and could be used in the fabrication of the next-generation molecular devices because of its ideal linear atomic nature. A large portion of long LCCs inside multi-walled carbon nanotubes (MWCNTs) were synthesized by atmospheric arc discharge in the presence of boron. Closed-end growth of MWCNTs in the arc process is suggested as a critical condition for the simultaneous growth of LCCs within the inner cores of carbon nanotubes. The strong Raman line around 1850 cm(-1) was used to characterize the degree of filling as well as their structural stability under high temperature thermal treatments. We observed a distinctive change in the electrical conductivity of the MWCNT assembly before and after the disappearance of LCCs due to the expected strong coupling interaction between the LCCs and the innermost tube. This work demonstrates for the first time the enhanced effect of confined linear carbon chains on the overall electrical conductivity of MWCNT assemblies. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: RAMAN-SPECTROSCOPY; HEAT-TREATMENT; ARC-DISCHARGE; POLYYNES; CARBYNE; COALESCENCE; TRANSITION; PARTICLES; DIFFUSION; TRANSPORT